2008
DOI: 10.1111/j.1872-034x.2008.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor in cooperation with SREBP‐1c is a major lipid synthesis regulator in nonalcoholic fatty liver disease

Abstract: These findings suggest that LXR acts as one of the main regulators of lipid metabolism by regulating SREBP-1c expression in NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(170 citation statements)
references
References 33 publications
9
150
0
Order By: Relevance
“…Recently studies have shown that the acyl-CoA synthetase activity plays a key role in altering AMPK activation (28). Thus, ACSL3 knockdown could potentially alter AMPK activation, which is known to regulate numerous transcription factors to control gene expression (29,30). However, neither total AMPK nor phosphorylation of AMPK at Thr-172 were changed by ACSL3 knockdown (Fig.…”
Section: Journal Of Biological Chemistry 30479mentioning
confidence: 82%
See 1 more Smart Citation
“…Recently studies have shown that the acyl-CoA synthetase activity plays a key role in altering AMPK activation (28). Thus, ACSL3 knockdown could potentially alter AMPK activation, which is known to regulate numerous transcription factors to control gene expression (29,30). However, neither total AMPK nor phosphorylation of AMPK at Thr-172 were changed by ACSL3 knockdown (Fig.…”
Section: Journal Of Biological Chemistry 30479mentioning
confidence: 82%
“…Increased rates of de novo lipogenesis in obesity (40), hyperlipidemia (41), fatty liver disease (29), and type 2 diabetes (41) subjects suggests that conversion of surplus carbohydrate to lipids modulates hepatic function and contributes to the development of steatosis, insulin resistance, and dyslipidemia. Fatty acids derived from de novo lipogenesis are preferentially incorporated into storage lipids such as TAG and secreted as very low density lipoprotein rather than mitochondrial oxidation (19,42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its oxidized derivative, oxysterol, is an agonist of liver X receptor (LXR), which transactivates lipogenic transcriptional factors, including sterol regulatory element-binding protein (SREBP)-1c and carbohydrate response element-binding protein (ChREBP) (15). However, …”
Section: Effects Of Nutritional Factors On the Expression Of Dpp4 Inmentioning
confidence: 99%
“…Moreover, enhanced hepatic lipid production is induced by IR. Hyperglycemia induces the transactivation of transcriptional factors, carbohydrate responsive element binding protein and Liver X receptor, which are known to activate de novo hepatic lipid synthesis (5,6). Furthermore, triglyceride hydrolysis in the liver is also modified by IR.…”
Section: Introductionmentioning
confidence: 99%